Evaluation of factors affecting service quality for MYBAS public transportation using : geographic information system / Solehah Mohamad Subri - Mohamad Subri, Solehah (2018)
This study about the problem that has from the myBAS Perlis. The problem is myBAS has a problem about passenger. In August 2015, myBAS was launch in Terminal Bukit Lagi, Kangar but in 2016 myBAS has a problem about passenger. This project aims to analyse the correlation of the myBAS based on factors affecting using GIS. The objective of this study is to determine the myBAS transportation routes in Perlis, to identify the influence factor affecting to the myBAS transportation and to analyse the relationship between routes and influence factor of the myBAS transportation using GIS approach. Network Analysis method is used for solve the problem. From Network Analysis method, can find the best routes for myBAS. For the other method for this study is used question survey. For this method was the respondents are selected randomly without looking into any specific criteria. However, the respondents were chosen from the passengers that ride on the buses on the study routes. All the respondent was 106 respondent in study area. Before find the best routes, firstly determine all rotes myBAS. Data population is a one factor of the influence in this problem. Lastly produce the best routes for myBAS Perlis map. In terms of overall satisfactions, the service performance level of myBAS Perlis. Although the system is efficient, it is still inadequate to attract people to use their service. Some improvements are needed in order to make buses as a preferred mode of travel.